Hide and seek - Messner, Kate (Scholastic Press, 2013)
For five hundred years the Jaguar Cup, sacred to the Silver Jaguar Society, was hidden in a cave on the coast of Costa Rica--so when a fake copy shows up on display in America, it is up to José, Anna, and Henry, junior members of the society, to travel to Costa Rica and rescue the real cup from thieves.